2021
DOI: 10.1002/lio2.556
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of the COVID‐19 pandemic on otolaryngologists: Should we be concerned?

Abstract: Objective Physicians on the frontline of the COVID‐19 pandemic are at increased risk of contracting the disease. Otolaryngologists are amongst the high‐risk practitioners, as they are in close proximity to patient's upper airway, which may induce their psychological stress. Methods A cross‐sectional survey study, conducted among otolaryngologists in Saudi Arabia from June 11 to June 22. Survey consisted of sociodemographic questionnaire, Coronavirus Anxiety Scale (CAS), Obsession with COVID‐19 Scale (OCS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(35 reference statements)
0
8
1
Order By: Relevance
“…In addition, the psychological effects of the epidemic were greater in females. Although some studies showed that males had more COVID-19 anxiety than females (e.g., Ashoor et al, 2021 ; Curtis et al, 2021 ; Saravanan et al, 2020 ), it was found that females had more in this meta-analysis.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…In addition, the psychological effects of the epidemic were greater in females. Although some studies showed that males had more COVID-19 anxiety than females (e.g., Ashoor et al, 2021 ; Curtis et al, 2021 ; Saravanan et al, 2020 ), it was found that females had more in this meta-analysis.…”
Section: Discussioncontrasting
confidence: 74%
“… Turkey Europe Medical 45.95 Collectivism Chorwe-Sungani, 2021 102 8 Malawi Africa Hospital staff 36.70 Collectivism García-Reyna et al, 2021 2140 5.5 Mexico North America Hospital staff 36.10 Collectivism Curtis et al, 2021 281 7.5 USA North America General population 64.69 Individualism Çakmak and Öztürk, 2021 162 N.A. Turkey Europe Hospital staff 36.9 Collectivism Ashoor et al, 2021 129 6 Saudi Arabia Middle East Hospital staff N.A. Collectivism Bhattacharya et al, 2021 154 N.A.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations